TANGGUNG JAWAB PEJABAT PEMBUAT AKTA TANAH (PPAT) DALAM PENANDATANGANAN AKTA JUAL BELI YANG DIDASARI ATAS BLANGKO KOSONG (CONTOH KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR 1201/K/PDT/2016) - Arlene .; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2018)
PPAT or The Land Deed Official is a Public Official who is granted part of the authorities by the State in the implementation of land registration and the making of an authentic deed. The certificate that is made by PPAT must be made based on the deeds of the law by the parties. The authentic certificate can be used as evidence in case of dispute based on the ordinance. According to Article 22 Regulation Number 37 of 1998, the certificate must be read by The Land Deed Official in front of the parties along with two witnesses. However, in this case, The Land Deed Official asked one party to sign on the blank certificate, as a result the certificate wasn’t being read in front of the parties. This deed is accused of maladministration that includes unlawful procedures, abuse of power, malfunction and unfairness or incompetence. The author examines the problem using normative legal research methods which supported by some interviews with the ones who are experts in the field of the land and maladministration. This deed resulted in the existence of legal consequences. The sanctions awarded againts to the Land Deed Official who did this deed contained in Ministerial Decree of Agrarian Affairs and Spatial/Head of National Land Authority Number 1 year of 2006 Article 28 paragraph (1) includes firing from The Land Deed Official membership.